2019
DOI: 10.1515/aut-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silicone-Modified Acrylate Latex and its Application for Low-Emission Printing of PET Fibre

Abstract: Attempts were made to find a more environmentally friendly technique for the printing of polyester (PET ) fabric, acting as an alternative to a usual disperse dye direct-printing process by using a plenty of water and salt and producing effluent contaminants. The low-emission printing technique includes the recipe containing disperse dye paste, synthetic thickener and the water-based silicone-modified acrylate and high-temperature curing process. The water-based silicone-modified acrylate for adhesive coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The excellent color fastness (≥level 4) in the low-emissivity printing process was achieved. A residual dye concentration was decreased by ~19 times as compared with traditional direct printing, while the effluent wastewater drainage was lowered by 76.9% [ 112 ].…”
Section: Modification Of Surface Properties Of Fibers and Textiles Wi...mentioning
confidence: 99%
“…The excellent color fastness (≥level 4) in the low-emissivity printing process was achieved. A residual dye concentration was decreased by ~19 times as compared with traditional direct printing, while the effluent wastewater drainage was lowered by 76.9% [ 112 ].…”
Section: Modification Of Surface Properties Of Fibers and Textiles Wi...mentioning
confidence: 99%
“…Acrylates are widely used in coatings due to their excellent film-forming properties and high adhesion to substrates. Silicone-modified acrylates have good mechanical properties, are resistant to heat and adverse weather conditions, and produce films with low surface energy [19][20][21]. After curing, the fluorine-containing side chains stretch at the interface, significantly reducing the film and conferring the polymer with strong water and oil repellency, improving the friction and corrosion resistance of the film [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of functional components with low solubility parameters and low surface energies is an effective way to weaken the PA binder‐disperse dye compatibility 38,39 . For example, Ai et al prepared silicon‐modified PA binder to improve the color fastness and color strength of the printed PET fabric 44 . Wang et al reported similar results that the color yield and fastness of the printed PET fabrics were enhanced when using silicon‐modified PA as a binder 38 .…”
Section: Introductionmentioning
confidence: 99%